Poromechanics II : proceedings of the second Biot Conference on Poromechanics, Grenoble, France, 26-28 August 2002 /: proceedings of the second Biot Conference on Poromechanics, Grenoble, France, 26-28 August 2002. (2020) - Unknown
No abstract available